Media statistika berbantuan scratch terintegrasi PBL: Solusi pembelajaran inovatif untuk meningkatkan berpikir kritis matematis siswa SMP - Neng Dewi Andryani; Nelly Fitriani; Linda (IKIP Siliwangi, 2026)
This study evaluated the feasibility of Scratch-assisted learning media integrated with a problem-based learning model to enhance junior high school students' critical mathematical thinking skills in statistics. Utilizing the ADDIE development framework, data collection was conducted in West Bandung Regency. The evaluation progressed through three distinct phases: a one-to-one trial with three students, a small-group trial with six students, and a field trial. The subsequent effectiveness test compared experimental and control classes, comprising 29 students each, utilizing a test instrumen of critical thinking skills. Data analysis was performed using descriptive and inferential statistics via Microsoft Excel and IBM SPSS 27. Expert validation demonstrated exceptional quality, with media experts rating the tool at 97.22% and material experts at 96.11%, both indicating high validity. Additionally, the media achieved a practicality rating of 82.00%. Regarding effectiveness, the experimental class showed a moderate improvement with an average N-gain of 64.41%, significantly outperforming the control class at 46.75%. The Mann-Whitney U test confirmed this significance Asymp. Sig. value < 0.001 < α = 0.05. Consequently, this integrated media is proven valid, practical, and effective.